THE ROLES OF HEALTH PROFESSIONS EDUCATION IN DEVELOPING ECO-ETHICAL LEADERSHIP - Susani, Yoga Pamungkas; Hartanti, Wika; Kristina, Susi Ari (Universitas Gadjah Mada, 2023)
Background: Climate change has become a global problem that has a wide impact on human life. It is a moral responsibility for humans to participate in protecting the earth and slowing the destruction of the earth. The role of medical and health profession education is important in producing health workers who are aware of the importance of protecting the environment and have leadership characteristics that are able to drive system change towards environmental improvement. This article is a recommendation from the I AM HPExplore Webinar Series 2022, Webinar #4. This article aims to provide literacy on the importance of eco-ethical leadership in medical and health education and how its development is included in the curriculum.Recommendation: Eco-ethical leadership is needed in the process of health professional education, especially in the process of forming future health workers who have these characteristics, so that they are able to bring health services that are more friendly to planetary health. The process of character building can be carried out at the individual, organizational, and system levels. In educational institutions, this step can be initiated by including it in the formal curriculum by inserting material into the existing curriculum, or by establishing a special learning program. Cultivating behaviors that support planetary health in the hidden curriculum can support character building. Conclusion: Planetary health is a global issue. For keeping the planet healthy, it requires mutual effort from the individual to the system level, multiprofessional and interdisciplinary collaboration, including from the field of education as a form of our moral responsibility. The formation of eco-ethical leadership needs immediate attention in the education of health workers.